The father of jihad 'Abd Allah 'Azzam's jihad ideas and implications to national security - Muhammad Haniff Hassan (Imperial College Press insurgency and terrorism series, 2014)
This study revolves around the jihad ideas of 'Abd Allah 'Azzam -- an iconic figure in the study of militant jihad in the 20th century, history of Afghan jihad against the Soviet Union, Al-Qaeda and current threat of terrorism.